2022
DOI: 10.3390/life12040545
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Fat Metabolism during Multi-Day High-Altitude Sojourns: A Hypothesis Based on Adipocyte Signaling

Abstract: Several publications and random observations have reported weight loss in high-altitude sojourners of both sexes. This could be a result of multiple adaptations, which hypoxia and mountaineering provoke on a cellular and organic level. Several publications have discussed the effect on appetite-regulating hormones to be one of the main contributing factors. We aimed to review the available data and show the current state of knowledge regarding nutritional aspects in high altitude with a special focus on fatty d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Despite having a high metabolism and engaging in regular physical activities, Jiarong Tibetans living at high altitudes did not experience a significant increase in BMI, WC, or lipid level in spite of consuming a high energy diet (3449.69 ± 843.70 kcal/d) ( Table 3 ). Notably, multiple studies suggested that weight loss resulting from exposure to high altitude hypoxic environments could be an effective method for reducing body fat in obese individuals ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a high metabolism and engaging in regular physical activities, Jiarong Tibetans living at high altitudes did not experience a significant increase in BMI, WC, or lipid level in spite of consuming a high energy diet (3449.69 ± 843.70 kcal/d) ( Table 3 ). Notably, multiple studies suggested that weight loss resulting from exposure to high altitude hypoxic environments could be an effective method for reducing body fat in obese individuals ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“… 125 At HA, leptin secretion was found to be increased in sojourns with exposure to hypoxia that showed peak at 10th day and eventually decreased after 14th day with prolonged hypoxia exposure (altitude). 126 Vats et al. 127 reported at 3600 m (Phase II), HA exposure reduces plasma leptin levels in human subjects on day 2 along with anorexia and drecreased body weight as compared to low altitude subjects (Phase I, 320 m).…”
Section: Mirna and Leptin Signaling Pathway At High Altitude...mentioning
confidence: 99%
“… 135 Under hypoxia, expression of leptin depends on the amount of white adipose tissue (WAT) with increased β‐oxidation of fatty acids, changes in fat mobilization, decreased triglyceride level, and with a concomitant increase in the fat uptake due to high‐fat diet in the course of high‐altitude sojourns. 126 A comparative study on sojourner and HA natives showed decreased serum leptin concentrations in native women living at a higher altitude as compared to women at low altitude with a protective effect on cardiometabolic outcomes in HA natives. 136 …”
Section: Mirna and Leptin Signaling Pathway At High Altitude...mentioning
confidence: 99%
“…In recent years, numerous studies have revealed that participants lost significant weight after they reach a plateau under hypoxic conditions [ 8 , 9 ]. Other investigations have also confirmed altitude is inversely associated with obesity prevalence [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%